Transcatheter Arterial Embolization in the Treatment of Maxillofacial Fractures With Life-Threatening Hemorrhage. Issue 6 (June 2018) - Matsumoto, Shokei; Akashi, Taku; Hayashida, Kei; Sekine, Kazuhiko; Orita, Tomohiko; Funabiki, Tomohiro; Kitano, Mitsuhide
Abstract : Introduction: Transcatheter arterial embolization (TAE) has gained importance in the management of maxillofacial fractures with life-threating hemorrhage (MFH). However, clinical evidence supporting the use of TAE has not been clearly established in the literature. Therefore, we evaluated the effectiveness of TAE for MFH, based on data obtained from the Japan Trauma Data Bank. Methods: Patients were identified from Japan Trauma Data Bank entries for the years 2004 to 2014. Inclusion criteria for MFH were defined using the Abbreviated Injury Scale code (Maxilla fracture, LeFort III; blood loss. > 20%). On the basis of the treatment strategy, patients were categorized into either the TAE group or the non-TAE group. A comparative analysis of the demographics, injury characteristics, and outcomes was performed. Results: From among 198, 744 documented cases of trauma, a total 118 patients were eligible for the study; 26 of these patients (22.0%) underwent TAE. The Glasgow Coma Scale score was significantly lower in the TAE group than in the non-TAE group ( P = 0.019); the other variables did not significantly differ between the groups. Overall, the in-hospital mortality rate was 39.8%, and the median hospital length of stay was 21.0 days (0.0–53.5 days). The in-hospital mortality was significantly lower in the TAE group than in the non-TAE group (23.1% vs 44.6%; odds ratio [OR], 0.37; 95% confidence interval [CI], 0.14–1.02; p = 0.048). However, patients in the TAE group had a longer median hospital length of stay (39.5 [7.3–53.5] vs 14.0 [0.0–55.3] days, p = 0.072). In the logistic regression model, the use of TAE was extracted as the independent predictor for better outcomes after adjusting for potential confounders (OR, 0.32; 95% CI, 0.66–0.88; P = 0.032). Hypotension, a high Injury Severity Score, aged 60 years or older, and a low Glasgow Coma Scale score were also independently associated with mortality, with an OR of 5.48, 3.99, 3.30, and 2.89, respectively. Conclusions: Cases of MFH are rare, but they are associated with a high mortality. Transcatheter arterial embolization use appears to lead to successful outcomes in such cases. Further studies are required to confirm the efficacy of TAE and evaluate its indications and complications.